İç Çatışma Sonrası Kolombiya’da Barış İnşası Süreci - Ceren UYSAL OĞUZ; E. Nur SEZEK (Gazi Akademik Bakış)
The armed conflict in Colombia with the FARC-EP that started in 1964, ended with the “Final Agreement to End the Armed Conflict and Build a Stable and Lasting Peace” in 2016 and the peacebuilding process began. The way to achieve a lasting peace is to implement the peace agreement and solve the problems of the conflict period and achieve the necessary social, political, and economic transformations. It is decided by the Colombian government and the FARC-EP to complete the implementation of the agreement in 15 years. The main points of the agreement are comprehensive rural reform; political participation; end of the conflict; solution to the illicit drugs problem; agreement regarding the victims of the conflict; implementation, verification and public endorsement. If the implementation process is not completed, the projected reforms would not be enough to achieve a lasting peace. This study analyses the implementation rates of the six main points of the agreement and examines the social, political, and economic reforms in the country within the framework of the following research question: “Could it be anticipated that the peacebuilding process in Colombia has progressed positively?” Moreover, the study discusses the reasons of the obstructions in the peacebuilding process. Findings of the study show that the implementation rates of the four main points of the agreement have been well below the target. However, it is observed that the progress of the social, political, and economic transformations has been positive.